Enhancing LQR and LQT Control Strategies for the Output Performance of PG36M555 DC Motors - Akhmad Azhar Firdaus; Nugraha, Anggara Trisna; Rama Arya Sobhita; Dhadys Ayu Juli Anjhani (SAINSTECH NUSANTARA, 2025)
A DC motor is commonly utilized as an actuator due to its ability to produce high torque. Controlling the motor's speed is one of the primary methods to manage its performance. Among various wireless communication options, radio waves are preferred since they do not require a clear line of sight between the transmitter and receiver. Employing multiple antennas offers benefits such as enhanced reliability and increased data transmission rates. This study focuses on designing and simulating four types of systems: SISO, SIMO, MISO, and MIMO. The performance of these configurations is evaluated and compared using Signal-to-Noise Ratio (SNR) and channel capacity, with variations in antenna count. Simulations were carried out in MATLAB to analyze how different antenna quantities (4, 8, and 16) affect channel capacity across an SNR range of 0 to 30 dB. The simulation outcomes reveal a substantial rise in system capacity, reaching up to 214 bits/Hz/sec when a 16x16 MIMO setup is applied at 30 dB SNR.